BENTUK DAN FUNGSI KATEGORI FATIS DALAM KOMUNIKASI LISAN BAHASA MELAYU DIALEK SUNGAI ROKAN - Gunawan Gunawan (JURNAL PENDIDIKAN ROKANIA, 2020)
In daily communication of among Native speakers of Malay language of Rokan dialect, which is very special because fatis can create and keep mantain the social relationship in communication. The importance of fatis in the communication of Malay dialect clearly seem that the position of fatis in many aspects namely, religion, customs, culture and manners. The theory uses is about Fatis category by Kridalaksana (1994), Malinowski in Sutami (2004. The method used in this study is a qualitative approach with descriptive research types. The research method is aimed at obtaining a description of the use of disclosure in the communi- cation of the Rokan River Malay Language. Forms of categorization of languages: Malay, Sungai Rokan dialect, District of regency, Regency of Rokan Hulu, consisting of 25 particles, 20 in the form of words, 15 in the form of form and 6 in the form of a square and a sentence The number of syrups will be added to follow the development and the need for discussion of the Spread community itself. The function of the anti-religious in the language The Malay Sungai Rokan dialect is not only to start, greet, confirm and maintain, in this thesis, researchers find 10 functions that are commonly used by the community of Sungai Rokan , including; pharynx functions to start, maintain, confirm, terminate, affirm, convince, admonish, praise, and fear / bully. From a group of forms, fatism in the language of living in the Sungai Rokan is very dominant using the particle, and functions, the dominant use of which is the function and ridicule. Based on the data analysis, it can be concluded that the Malay language of the Rokan River Dialect has 60 forms of phisic categories and the phisic form of the particle is phatic which is often used. In terms of function, the Malay language of the Rokan River Dialect has 10 phatic functions and the dominant one is the affirmative and mocking function.